Poised Scheduling of Flash Crowd Cellular Traffic in LTE and LTE-A for Optimal Load Balancing - Madhu Ramarakula, Shaik.Riyazuddien, Dhulipalla.Venkata Rao (International Journal of Advanced Science and Technology, 2020)
Rapid increase in the demands of services for wireless communication pose novel challenges in forthcoming cellular networks generation design. Here, in LTE (Long term evolution) and LTE-A (LTE-Advanced) networks, effective load balancing of flash crowd cellular traffic at both up and downlinksis a crucial challenge to achieve the effective quality of service with minimal communication (text, audio, and video) drop and maximal throughput.Hence, contemporary researchers have eyed to lighten the importance of load balancing to achieve the quality of service over LTE and LTE-A networks. Poised Scheduling of flash crowd cellular traffic has portrayed in this manuscript, which aimed to achieve the quality of service by optimizing the balancing of the load appeared on target networks of LTE and LTE-A. The simulation-based experimental study anticipated the significance of the proposed model that scaled by comparing with other contemporary scheduling models of the LTE, and LTE-A network traffic.